2016
DOI: 10.1371/journal.pone.0159593
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetic Factors Involved in Celiac Disease, Type 2 Diabetes and Anorexia Nervosa Suggest Common Molecular Pathways for Chronic Diseases

Abstract: Background and ObjectivesGenome-wide association studies (GWAS) have identified several genetic regions involved in immune-regulatory mechanisms to be associated with celiac disease. Previous GWAS also revealed an over-representation of genes involved in type 2 diabetes and anorexia nervosa associated with celiac disease, suggesting involvement of common metabolic pathways for development of these chronic diseases. The aim of this study was to extend these previous analyses to study the gene expression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The studies have found hazard ratios for the development of celiac disease in those already diagnosed with AN ranging from 2.18 (95% CI [1.45–3.29]) to 3.08 (95% CI [2.11–4.34]) and the development of AN in those previously diagnosed with celiac of 1.46 (95% CI [1.08–1.98]) to 2.46 (95% CI [1.4–4.03]) (Marild et al, 2017; Wotton et al, 2016). One genetic study, by Mostowy et al (2016), also found shared genetic factors between the two diseases.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The studies have found hazard ratios for the development of celiac disease in those already diagnosed with AN ranging from 2.18 (95% CI [1.45–3.29]) to 3.08 (95% CI [2.11–4.34]) and the development of AN in those previously diagnosed with celiac of 1.46 (95% CI [1.08–1.98]) to 2.46 (95% CI [1.4–4.03]) (Marild et al, 2017; Wotton et al, 2016). One genetic study, by Mostowy et al (2016), also found shared genetic factors between the two diseases.…”
Section: Resultsmentioning
confidence: 98%
“…Several studies are indeed suggestive of a bidirectional relationship between celiac disease and AN (Hedman et al, 2019;Marild et al, 2017;Nacinovich et al, 2017;Wotton et al, 2016 (Marild et al, 2017;Wotton et al, 2016). One genetic study, by Mostowy et al (2016), also found shared genetic factors between the two diseases.…”
Section: Celiac Diseasementioning
confidence: 98%
“…Therefore, presence of type 2 diabetes should not be taken as a reason for not screening for celiac disease. There has also been suggestion for screening for celiac disease in type 2 diabetes mellitus 29,30 . Osteoporosis or osteopenia which is also well recognized in celiac disease 31 , was seen in 12% of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, due to shared genetic regions between EDs and autoimmune diseases (Mostowy et al, 2016), some other studies had focused on the prevalence and risk of CD in patients with EDs.…”
Section: Introductionmentioning
confidence: 99%